2015
DOI: 10.1007/s00464-015-4390-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and economic outcomes between robotic, laparoscopic, and open rectal cancer surgery: early experience at a tertiary care center

Abstract: The findings demonstrate similar perioperative and short-term outcomes between robotic surgery and conventional approaches. Robotic assistance is associated with decreased intraoperative blood loss and fewer conversions, albeit at an increased overall cost. Given these benefits, and as data and experience mature, future study is needed to fully define the value of the robotic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 8 publications
(8 reference statements)
2
91
0
1
Order By: Relevance
“…[10,11,1417,19,23,25,26,29] Three studies [14,16,25] showed that EBL was lower for RTME than LTME, although no significant difference was found in the rest of studies. Pooled data analysis revealed that there was no significant difference in EBL between the techniques [WMD = −12.45, 95% CI (−48.66 to 23.76), P  = .500], with a high heterogeneity (I 2  = 75.9%; P  < .001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,11,1417,19,23,25,26,29] Three studies [14,16,25] showed that EBL was lower for RTME than LTME, although no significant difference was found in the rest of studies. Pooled data analysis revealed that there was no significant difference in EBL between the techniques [WMD = −12.45, 95% CI (−48.66 to 23.76), P  = .500], with a high heterogeneity (I 2  = 75.9%; P  < .001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies [1014,16,19,2426,28,29] showed rate of conversion to open procedure. Overall, no significant difference was found between techniques, except in 1 study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to assess whether the difference in conversion rate with robotic surgery warrants widespread adoption of this technique given the increased cost. Ramji and colleagues 28 report on a Canadian series comparing robotic, laparoscopic and open rectal cancer resections. They found an incremental cost difference of approximately $6000 per case for robotic resections versus either laparoscopic or open resections.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cancer surgery in locally advanced stages is associated with more blood loss; longer operation duration; more concomitant organ resections; and more postoperative complications such as anastomotic leakage, pelvic floor dysfunction, incontinence and genitourinary problems. However, robotic rectal resection may improve perioperative outcomes, such as reduction of perioperative blood loss, and is being explored 177 .…”
Section: Managementmentioning
confidence: 99%